2014
DOI: 10.1002/bip.22532
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembly of regenerated silk fibroin from random coil nanostructures to antiparallel β‐sheet nanostructures

Abstract: In this work, we studied the effects of incubation concentration and time on the self-assembly behaviors of regenerated silk fibroin (RSF). Our results showed the assembly ways of RSF were concentration-dependent and there were four self-assembly ways of RSF: (i) At relatively low concentration (≤0.015%), RSF molecules assembled into protofilaments (random coil), and then the thickness decreased and the secondary conformation changed to antiparallel β-sheet; (ii) at the concentration of 0.015%, RSF molecules a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 78 publications
(129 reference statements)
10
51
0
Order By: Relevance
“…Some studies suggested the direct transition from a random-coil structure to a β-sheet one. 6,8,11 In contrast, other studies suggested transition models through intermediates. 7,9 By X-ray scattering under shear and IR absorption measurements, the transition from an amorphous β-sheet structure to a β-turn-rich crystalline Silk I one was observed as an intermediate process before the formation of silk fibers.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Some studies suggested the direct transition from a random-coil structure to a β-sheet one. 6,8,11 In contrast, other studies suggested transition models through intermediates. 7,9 By X-ray scattering under shear and IR absorption measurements, the transition from an amorphous β-sheet structure to a β-turn-rich crystalline Silk I one was observed as an intermediate process before the formation of silk fibers.…”
Section: Introductionmentioning
confidence: 91%
“…4 Thus, much attention has been focused on the mechanism of the structural transition from liquid silk to silk fibers not only to understand the structural origin of the expression of their excellent mechanical properties and biocompatibility but also to develop materials that are more advanced than silk fibers. [5][6][7][8][9][10][11] For the spectroscopic study of the mechanism, silk fibroin concentrated aqueous solutions that are formed by the lysis of silk fibers in LiBr or CaCl2/C2H5OH solutions at high temperatures, called regenerated silk fibroin solutions, have been used. [6][7][8][9]11 By electronic circular dichroism (ECD) and infrared (IR) absorption measurements and X-ray scattering and NMR ones under shear, it was observed that regenerated silk fibroin solutions adopted a random-coil structure and they were converted into crystalline fibers with a Silk II structure, which mainly comprised a β-sheet structure.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations